Human Resources in China - Devonshire-Ellis, Chris; Scott, Andy; Woollard, Sam (China Briefing, The Practical Application of China Business, 2011)
Due to the rapidly changing nature of the labor market and the laws that govern it in China, it can be very difficult for foreign investors and managers to understand how to manage human resources on the mainland. Specifically designed to cover the most important issues relating to managing a Chinese workforce, this guide details the HR issues that both local managers in China and investors looking to establish a presence on the mainland should know. China Briefing?s guides are leaders in their field, providing practical and pragmatic legal and tax information to foreign investors in the People's Republic of China. They will interest all business people, lawyers, accountants and academics working in the field.